Penerapan Lesson Study pada Kegiatan Praktikum Mikrobiologi Program Studi Pendidikan Biologi IKIP Budi Utomo Malang - TRIO AGENG PRAYITNO; NURIL HIDAYATI (Bioedukasi: Jurnal Pendidikan Biologi, 2016)
Microbiology course is one of the compulsory subjects in the study program of education. This course requires implemented in two activities that is theory and practical. Limitations of equipment and materials in practical activities, the lack of detailed practical instructions for each topic, as well as the implementation of lab activities less systematically make this activity less than optimal. The development of psychomotor abilities and performance of students who are less maximized become another problem related to the achievement of learning objectives in accordance with the standards of competence in this course. Based on the above problems the researchers conducted a study on lab activities based lesson study. Selection of lesson study is done to correct deficiencies in each study appears from some observers and colleagues who participated in the activities of lesson study. Results from this study that practical activities based lesson study is able to improve the quality of learning and improving biology education students psychomotor ability at IKIP Budi Utomo Malang